Essential Features of Process Fluids Applied in Machining - Jersak, Jan; Zizka, Jan (Manufacturing Technology Journal, 2015)
Not only engineering production at present is characterized by increasing an international competition. It is achieved higher productivity with simultaneous improvement of quality parameters of machined parts by using of process fluids. In other words, the use of process fluids positively improves and increases the both the qualitative as well as quantitative parameters of the technological processes. Process liquids in machining occupy an important place and influence the outcome of the all processes. Choosing a suitable process fluid should be carefully considered. It is well known that, different machining technologies have different cutting conditions and thus completely different requirements on process fluids. Selection of a suitable process fluid is more important that the management of manufacturing companies admits. Unfortunately, the selection of suitable process fluids is very often underestimated.
Keywords: machining process; process fluids; lubrication; cooling